2001
DOI: 10.4269/ajtmh.2001.64.49
|View full text |Cite
|
Sign up to set email alerts
|

Comparative neurovirulence of attenuated and non-attenuated strains of Venezuelan equine encephalitis virus in mice.

Abstract: Abstract. A candidate live-attenuated virus vaccine for protection against Venezuelan equine encephalitis (VEE) (designated V3526) was tested in mice to measure the magnitude, duration, and kinetics of virus replication in the blood and the central nervous system and its phenotypic stability after multiple passages in mice and cell culture. All results were compared to parallel experiments with parental virus and the existing VEE virus vaccine, TC-83. Maximum virus titers in the brains of V3526-inoculated mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 17 publications
5
51
0
Order By: Relevance
“…The phenotypic properties of the viruses generated from clones in this study and in past studies [17,19,21,[26][27][28][29][30] provide the formal evidence that the identified single mutations were responsible for the observed attenuation. From the list of mutations, vaccine candidates for VEEV were constructed to provide a higher level of attenuation and a mathematical improbability of reversion to wild-type phenotype after production and vaccination.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The phenotypic properties of the viruses generated from clones in this study and in past studies [17,19,21,[26][27][28][29][30] provide the formal evidence that the identified single mutations were responsible for the observed attenuation. From the list of mutations, vaccine candidates for VEEV were constructed to provide a higher level of attenuation and a mathematical improbability of reversion to wild-type phenotype after production and vaccination.…”
Section: Discussionsupporting
confidence: 62%
“…Based on our results in non-human primates and those from cohort studies in rodents [17,[28][29][30] and mosquitoes [32], V3526 was selected for development into a human-use vaccine. These other studies, like this study, showed V3526 to be more safe, immunogenic and efficacious than TC-83, and without any indication of reversion to virulent phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the cleavage deletion mutation (24) and attenuated phenotype of the virus prompted the evaluation of V3526 as a vaccine for animals and humans (34,37,52,53). In the course of preclinical evaluation of V3526 as a live vaccine, a series of MAbs were generated to further characterize the immune response elicited by vaccination with V3526.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the PE2 cleavage signal deletion is lethal to the virus and requires a second site mutation, a Ser for Phe at E1 codon 253 in V3526, for viability. V3526 has been shown to be safe [8] and to protect mice against subcutaneous or aerosol challenge with a virulent VEEV-IA/B [9]. Recently, Pratt et al [10] reported that out of several vaccine candidates examined, V3526 was best able to protect nonhuman primates against aerosol challenge with a virulent VEEV-IA/B.…”
Section: Subject Termsmentioning
confidence: 99%